The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1088/0964-1726/16/6/069
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and viscoelastic properties of anisotropic magnetorheological elastomers

Abstract: The microstructures and viscoelastic properties of anisotropic magnetorheological elastomers are investigated. The measurement results show that their mechanical properties are greatly dependent on the magnetic flux density applied during preparation. A finite-column model is proposed to describe the relationships between the microstructures and the viscoelastic properties. The simulation results agree well with the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
166
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(186 citation statements)
references
References 15 publications
8
166
1
Order By: Relevance
“…MR elastomer is the solid-state analogue of MR fluid, and a new branch of MR materials [9][10][11][12][13][14][15]. The problems existing in MR suspensions such as particle sediment are well overcome via replacing the fluid matrix by a solid matrix such as a polymer.…”
Section: Introductionmentioning
confidence: 99%
“…MR elastomer is the solid-state analogue of MR fluid, and a new branch of MR materials [9][10][11][12][13][14][15]. The problems existing in MR suspensions such as particle sediment are well overcome via replacing the fluid matrix by a solid matrix such as a polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental observations have found that both the shear modulus (e.g. Jolly et al, 1996;Zhou, 2003;Chen et al, 2007) and tensile modulus (e.g. Bellan & Bossis, 2002;Varga et al, 2006;Abramchuk et al, 2007) of these materials increase under a magnetic field, as shown in Fig.…”
Section: Literature Reviewmentioning
confidence: 90%
“…This indicates that the MR effect is high when the distances between the iron particles are close to each other due to the low strain. Chen et al [16] reported that the anisotropic MRE applied with a magnetic field of 1T during curing exhibited the 1200% higher MR effect than the isotropic MRE. However, the difference was not clear in this study.…”
Section: Mrementioning
confidence: 99%
“…Chen et al [15] observed that the addition of carbon black increased the mechanical properties of MREs and showed higher MR effect. Regarding the arrangement of iron particles, Chen et al [16] observed higher MR effect in anisotropic MREs than isotropic MREs. Especially, as the magnitude of the applied magnetic field increased (up to 1 Tesla), thicker chain structures were formed and the MR effect was high.…”
Section: Introductionmentioning
confidence: 99%